Financing micro and medium sized enterprises through decreasing partnership (musharakah mutanaqisah): refining shari'ah and banking aspects for enhanced applicability - Sadique, Muhammad Abdurrahman (Islamic Research & Training Institute, Islamic Development Bank, 2008)

(untitled)
Decreasing partnership as proposed by contemporary scholars could be effectively employed in financing MMEs, for procurement of assets as well as financing complete ventures. Its significance in financing MMEs could be enhanced through giving further prominence to the basis of equity participation, allowing the ancillary contracts of ijarah and sale to function independently. The paper argues that the reality of the underlying contracts should be effectively highlighted through pricing the units and ijarah rentals realistically, rather than as an apportionment of the profit element calculated on the capital outlay. In financing ventures on decreasing partnership, expenses of the venture should be shared proportionately; profit share of the bank should decline corresponding to the bank 19s stake, and unit price of the bank 19s share could be fixed based on a price negotiated at the time or professional valuation. The paper seeks to highlight many other conditions that are often violated in practice but that must be fulfilled in order to ensure full Shari'ah compliance.